Terapia analítico-comportamental: contribuições para a sistematização - ALVES, Thallyssa Raquel Soares (2019)
With the growing movement of evidence-based practice in psychology, there are concerns about the empirical support of the clinical psychologist's practice. Recent studies have shown that the exclusively Brazilian practice of Behavioral-Analytic Therapy (TAC) lacks empirical evidence to support it, moreover, the fact that it has never been normalized in the format of an intervention manual makes its replication impracticable and, consequently, prevents it from being empirically tested. It is also observed a plurality of the behavioral therapy scenario in Brazil, where different names have been used for practices that have more similarities than differences, which may be making it difficult to clarify the analytic-behavioral therapist's identity. In this sense, this research proposed to contribute to the normalization process of the TAC, identifying its main characteristics, such as the elaboration of the contingencies analysis, therapeutic objectives and techniques, in partnership with the therapists responsible for its development. In the first phase of this research, a survey was made with behavioral therapists from different regions of the country in order to create a list of 20 names of other therapists that best represented the TAC. In the second phase, three therapists mentioned in the list filled two forms, the first one of personal characterization of the participants containing sociodemographic questions, such as sex and age, as well as questions related to education and career, such as areas in which they work and therapeutic model mainly used; the second form contained three questions and aimed to understand the practice of analytical-behavioral therapists from the presentation of a clinical case and formulation of contingencies analysis, therapeutic objectives and techniques that the therapist would use in the case. The results showed, on the elaboration of contingency analysis, that the forms of presentation follow, in general, the evolution of the models presented in the literature about the instrument; that the formulated therapeutic objectives presented similarities and differences and, in the case of the mentioned techniques, the insufficiency of the description of clear procedures was noted. It was concluded that the practice of therapists reflects the absence of a basic manual for the practice of TAC, and that behavioral-analytic therapists, in general, may be acting in very different ways against the same clinical problems.